2016
DOI: 10.1155/2016/9485163
|View full text |Cite
|
Sign up to set email alerts
|

Sound Transmission in a Duct with Sudden Area Expansion, Extended Inlet, and Lined Walls in Overlapping Region

Abstract: The transmission of sound in a duct with sudden area expansion and extended inlet is investigated in the case where the walls of the duct lie in the finite overlapping region lined with acoustically absorbent materials. By using the series expansion in the overlap region and using the Fourier transform technique elsewhere we obtain a Wiener-Hopf equation whose solution involves a set of infinitely many unknown expansion coefficients satisfying a system of linear algebraic equations. Numerical solution of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…He showed that the sudden discontinuity in a cylindrical duct is analogous to lumped impedance. The transmission of sound in the case where the walls of the duct with sudden area expansion and extended inlet, treated by acoustically absorbing materials of finite length, is investigated by Demir (2016). In another work Demir (2017) defined the scattering matrices with the help of the Wiener-Hop technique in a non-uniformly lined duct with an inserted expansion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that the sudden discontinuity in a cylindrical duct is analogous to lumped impedance. The transmission of sound in the case where the walls of the duct with sudden area expansion and extended inlet, treated by acoustically absorbing materials of finite length, is investigated by Demir (2016). In another work Demir (2017) defined the scattering matrices with the help of the Wiener-Hop technique in a non-uniformly lined duct with an inserted expansion chamber.…”
Section: Introductionmentioning
confidence: 99%